Effects of piston geometry and injection strategy on the capacity improvement of waste heat recovery from RCCI engines utilizing DOE method. (April 2019) - Nazemian, Mehrdad; Neshat, Elaheh; Saray, Rahim Khoshbakhti
Highlights: Waste heat recovery from exhaust gases and coolant of a RCCI engine is studied. The effects of geometrical parameters on waste heat recovery are investigated. The interaction between geometrical parameters are investigated by DOE method. The bowl depth has more significant effects on irreversibility. The bowl depth could provide negative effects on the second law efficiency. Abstract: Internal combustion engines are used as one of the main components in many co-generation systems. Given the importance of exergy destruction in cogeneration systems, internal combustion engines must also be optimized from the point of view of entropy generation. The reactivity controlled compression ignition engines have the advantages of high thermal efficiency and low exhaust nitrogen oxides and particulate matter emissions. The main purpose of current study is optimization of the geometry of the combustion chamber based on second law analysis. The engine is simulated utilizing a computational fluid dynamics model and the effects of size of bowl depth, piston bowl diameter, pip height, throat diameter and top land height on exergy destruction are investigated. The design of experiments method is applied and the interactive effects of different factors on waste heat recovery and engine irreversibility are studied. Two different injection strategies including single and double injection are applied and the role of injection strategy on exergy destruction is studied. The results shows that using both of injection strategy, bowl diameter and bowl depth have the most significant effect on the capacity of waste heat recovery from exhaust gases.